Implementasi Sistem Pembayaran Air Berbasis Aplikasi sebagai Solusi Penurunan Tunggakan Konsumen - Puja Dwi Ramadhani; Fajar Syaiful Akbar (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study aims to evaluate the effectiveness of implementing an application-based water payment system as a strategy to reduce consumer arrears. Payment delinquency remains a significant challenge in the management of water utility services, often driven by low payment discipline, limited access to transaction channels, and the inefficiencies of conventional manual systems. Employing a quantitative approach, this research utilizes comparative data collected before and after the implementation of the digital payment application, supported by statistical analysis to measure changes in consumer payment compliance. The findings indicate that the adoption of an application-based payment system has a substantial positive impact on reducing arrears, as reflected in increased payment timeliness and a decline in the number of delinquent consumers. Features such as ease of access, automated notifications, and transparent billing information are proven to enhance consumer compliance behavior. These results underscore that the digitalization of payment systems can serve as an effective solution for improving operational efficiency and supporting the sustainability of water utility services.